FLASH CARD SEX EDUCATION BERBASIS AUGMENTED REALITY UNTUK ANAK PADA TAHAP PRA-OPERASIONAL - Oktavia Hardiyantari; Soraya Fatmawati (Universitas Muria Kudus, 2021)
The purpose of this study is to develop an interactive learning media in the form of an Augmented Reality (AR)-based flashcard that is used to introduce sexual education to children at the pre-operational stage or early childhood and determine its feasibility level.The research method used is the Research and Development (R and D) method. The stages of development using the Sugiyono model, namely: 1). Potential and problems, 2). Data collection, 3). Product design, 4). Product validation, 5). Design revision, 6). Product trial. Data collection techniques in this study are observation and questionnaires. Subjects at the product trial stage were 4 children. The data analysis technique used in this research is by using descriptive analysis techniques. There are three instruments used in this study, namely instruments for media experts, material experts and instruments filled out by parents.The results showed that AR-based Flashcard Sex Education for children in the pre-operational stage was considered very good by media experts with a score of 80.36%%. The results of the validation by material experts showed a score of 92.86% which means very good. The results of the trial on 4 early childhood children also showed very good results with a score of 92.05%. So based on the scores obtained, it shows that the AR-based Sex Education Flashcard is feasible and can be used as a learning medium.